Integral Representations for Spectral Functions of Some Nonself-Adjoint Jacobi Matrices - Zagorodnyuk, S.M. (Інститут математики НАН України, 2009)
We study a Jacobi matrix J with complex numbers an, n belongs Z+, in the main diagonal such that r0 ≤ Im an ≤ r1, r0, r1 belongs Z+. We obtain an integral representation for the (generalized) spectral function of the matrix J. Themethod of our study is similar to Marchenko’s method for nonself-adjoint differential operators.